Bilateral agreement for the academic year 2013/2014 Lifelong Learning Programme : higher education between Universitat Politècnica de València and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities shown below within the LLP/programme. - Subject area: Architecture, urban and regional planning.